2016
DOI: 10.1016/j.virusres.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, antigenicity and pathogenicity of global porcine epidemic diarrhea virus strains

Abstract: Emerging and re-emerging coronaviruses cause morbidity and mortality in human and animal populations, resulting in serious public and animal health threats and economic losses. The ongoing outbreak of a highly contagious and deadly porcine epidemic diarrhea virus (PEDV) in Asia, the Americas and Europe is one example. Genomic sequence analyses of PEDV variants have revealed important insights into the evolution of PEDV. However, the antigenic variations among different PEDV strains are less explored, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
250
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(264 citation statements)
references
References 136 publications
(228 reference statements)
12
250
1
1
Order By: Relevance
“…However, we speculated otherwise because the reported PEDV strains PC177-P2 and Tottori2 possessing the same deletions found in the variants of this study could replicate well in cell culture and cause cytopathic effect [17, 19]. Besides, the mutant strain PC177-P2 can propagate well and induce diarrhea in piglets [43]. A deletion of 215 aa (position 19–233) in the N-terminal domain of the S protein analogous to the deletion observed in the variants revealed a not impaired propagation of PEDV in vivo [44].…”
Section: Resultsmentioning
confidence: 99%
“…However, we speculated otherwise because the reported PEDV strains PC177-P2 and Tottori2 possessing the same deletions found in the variants of this study could replicate well in cell culture and cause cytopathic effect [17, 19]. Besides, the mutant strain PC177-P2 can propagate well and induce diarrhea in piglets [43]. A deletion of 215 aa (position 19–233) in the N-terminal domain of the S protein analogous to the deletion observed in the variants revealed a not impaired propagation of PEDV in vivo [44].…”
Section: Resultsmentioning
confidence: 99%
“…G2 was further divided into G2‐1 and G2‐2, and G1 was divided into G1‐1, G1‐2 and G1‐3 as shown in Figure . G1‐1 includes the prototype European strain CV777, other global historic S INDEL strains isolated between 1970 and 2010 (Lin et al., ), and vaccine strains that were developed in Asian countries such as KPEDV‐9 and attenuated DR13 from South Korea, P5‐V from Japan and attenuated CV777 from China. One Vietnamese strain (VN232/HB2013) in this study was clustered into this subgroup, and it was closely related to the previously reported Vietnamese strain HUA‐PED67 (2013) and Chinese strains CH7 (2011), JS‐2004‐2 (2004) and LJB03 (2006).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the sequence of the initial prototype strains in North America (high virulent NA prototype strains), the Vietnamese field strains VN262/HB/2014 and VN232/2013 possessed three deletions (a 1‐nucleotide deletion at position 166, an 11‐nucleotide deletion at positions 172–182 and a 3‐nucleotide deletion at positions 414–416) and a 6‐nucleotide insertion between positions 474 and 475 in the S gene. These insertions and deletion in the S gene are typical for the S INDEL type of PEDV (Vlasova et al., ; Lin et al., ). Of note, two classical Japanese strains in G1‐2 (NK and KH) do not possess these typical INDELs in the S gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations